Sensory Feedback in Hand Prostheses: A Prospective Study of Everyday Use - Wijk, Ulrika; Carlsson, Ingela K.; Antfolk, Christian; Björkman, Anders; Rosén, Birgitta (Frontiers in Neuroscience, 2020)
Introduction Sensory feedback in hand prostheses is lacking but wished for. Many amputees experience a phantom hand map on their residual forearm. When the phantom hand map is touched, it is experienced as touch on the amputated hand. A non-invasive sensory feedback system, applicable to existing hand prostheses, can transfer somatotopical sensory information via phantom hand map. The aim was to evaluate how forearm amputees experienced a non-invasive sensory feedback system used in daily life over a 4-week period. Methods This longitudinal cohort study included seven forearm amputees. A non-invasive sensory feedback system was used over 4 weeks. For analysis, a mixed method was used, including quantitative tests (ACMC, proprioceptive pointing task, questionnaire) and interviews. A directed content analysis with predefined categories sensory feedback from the prosthesis, agency, body ownership, performance in activity, and suggestions for improvements was applied. Results The results from interviews showed that sensory feedback was experienced as a feeling of touch which contributed to an experience of completeness. However, the results from the questionnaire showed that the sense of agency and performance remained unchanged or deteriorated. The ability to feel and manipulate small objects was difficult and a stronger feedback was wished for. Phantom pain was alleviated in four out of five patients. Conclusion This is the first time a non-invasive sensory feedback system for hand prostheses was implemented in the home environment. The qualitative and quantitative results diverged. The sensory feedback was experienced as a feeling of touch which contributed to a feeling of completeness, linked to body ownership. The qualitative result was not verified in the quantitative measurements. Clinical Trial Registration Name: Evaluation of a Non-invasive Sensory Feedback System in Hand Prostheses. Date of registration: March 15, 2019. Date the first participant was enrolled: April 1, 2015. ClinicalTrials.gov Identifier: NCT03876405 ORCID ID: https://orcid.org/0000-0002-4140-7478.